Philosophy of Education in Western and Islamic Perspectives - Rosyidin, Muhammad Abror; Haris, Abd (Tebuireng: Journal of Islamic Studies and Society, 2024)
Philosophy and philosophy of education cannot be separated; both have a very close relationship. Moreover, the philosophy of Islamic education undeniably has a connection with Western educational philosophy as an initial inspirator of the philosophical movement in Islam. This research is a qualitative study with a literature review. The data is taken from various related literatures. The focus is on (1) the relationship between Philosophy and Philosophy of Education, (2) the historical development of Western philosophy of education, (3) the historical development of Islamic philosophy of education, and (4) the comparison of Western and Islamic philosophy of education. The results are: (1) philosophy of education is defined as a normative science in the domain of education, (2) philosophy of education focuses on two normative scientific functions: formulating the foundation, goals, and understanding of the nature of humans, as well as the essence of the realm of education, (3) Western philosophy of education tends to emphasize education oriented towards progress and prioritizes logic, (4) Islamic philosophy of education emerged due to the advancement of Islam during the Abbasid golden age, (5) the similarities between Western and Islamic philosophy of education lie in nativistic, empiricist, and convergence theories, while the differences are that Western philosophy is anthropocentric and Islamic philosophy is theocentric, Western philosophy is based on human thought, Islamic philosophy is based on revelation dialogued with reason, Western philosophy focuses on knowledge, Islamic philosophy bases itself as a religion, Western philosophy considers evaluation to be done by oneself and others, while Islamic philosophy it to be done by oneself, others, and God.